1999
DOI: 10.1001/archpedi.153.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Weapon Carrying on School Property Among Middle School Students

Abstract: Objective: To examine the association between carrying a weapon at school and the age of onset of substance use, other indicators of violence, and other health risk behaviors among middle school students.Design: In 1995, a modified version of the Centers for Disease Control and Prevention Youth Risk Behavior Survey was administered to 2227 students (49% were female) attending 53 (of 463) randomly selected middle schools in North Carolina. Weapon carrying on school property during school hours was measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
3
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 30 publications
9
55
3
1
Order By: Relevance
“…In Table 4, we report incident level characteristics for all youth (analyses were run separately for younger [ages 2-9] and older [ages [10][11][12][13][14][15][16][17] youth with similar findings-not shown in Table): Weapon-involved incidents were more likely to be part of an indirect only victimization or an incident that involved both direct and indirect forms of victimization (rather than direct only). Weaponinvolved victimizations were more likely to be perpetrated by a peer, and result in injury.…”
Section: Incident-level Characteristics and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 4, we report incident level characteristics for all youth (analyses were run separately for younger [ages 2-9] and older [ages [10][11][12][13][14][15][16][17] youth with similar findings-not shown in Table): Weapon-involved incidents were more likely to be part of an indirect only victimization or an incident that involved both direct and indirect forms of victimization (rather than direct only). Weaponinvolved victimizations were more likely to be perpetrated by a peer, and result in injury.…”
Section: Incident-level Characteristics and Outcomesmentioning
confidence: 99%
“…Despite its relevance to public health, extant research on youth firearm exposure has focused on weapon carrying as the primary focus of exposure. [3][4][5][6][7][8][9][10] However, youth are also exposed to firearms and other weapons through direct victimization and witnessing violence; understanding how often and in what ways this occurs is critical to the field's broadening conceptualization of youth victimization.…”
Section: What This Study Addsmentioning
confidence: 99%
“…This might be especially salient to the present study as weapon carrying has been found to be most predominant for young people in the 13-to-16 year age range (DuRant, Krowchuck, Sinal, & Woods, 1999). Additionally, despite inconsistent evidence for the influence of gender on ISV perpetration (see Minnett, Vandell, & Santrock, 1983;Roscoe et al 1987), it is widely acknowledged that differences exist between adolescent males and females, for their use of both physical violence and weapons (Brennan & Moore, 2009).…”
mentioning
confidence: 74%
“…In addition to males more likely to carry handgun than females (Pickett et al, 2005), research has identified racial and ethnic differences. Studies in the U.S. indicate that African-Americans and Latinos are more likely to carry weapons such as handguns compared to Whites and Asians (e.g., Craun & Detar, 2015;Durant, Krowchuk, Kreiter, Sinal, & Woods 1999;Spano, 2012) in part because of more extensive and greater duration of involvement in criminal violence (Bierie, 2014;Craun & Deter, 2015;Doherty & Ensminger, 2014). However, there is a relative dearth of nationally representative studies on racial/ethnic differences in handgun carrying among youth.…”
Section: Introductionmentioning
confidence: 99%